(3GdLhgQ GdfVjO aj TQM GdJLQjOs - (3GdMdj, CHh efUhQ, GHf GdeWgQ, LeGd GdOjf, GdMSf Hf jhSa Hf Ydj GHf GdeWgQ, J (B726(3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdeJaQO HhLhH GdhLhO GeG HYO , jbhd GdMSf Hf jhSa Hf GdeWgQ Ef Gddg JYGdi deG habfj ddGSJaGOI ef TjNfG eMeO Hf GdMSf GdWhSj hbaJ Ydi eNJUQg GdeQShe HGdJLQjO aj Yde GdefWb aTQYJ aj GedGA gPG GdcJGH GdeQShe HGdLhgQ GdfVjO aj TQM GdJLQjO s
(3BNQgG (B:s
(3h GdNWGHj hGdBQGA GdeMehOI dCf GdeNdGJ cdeG cGfJ CdP hCYLH adG jecf VHW GdehGVjY aj GdUfGYJjf GdChdJjfs
(3GdNWhW eNJdags
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B2 / 227s
(3eYLe GdeDdajf (B1 / 598s
(3cTa GdXfhf (B1/ 346s
(3GdOQQ GdcGefI (B2 / 71s
Keywords: (3GdadSaI hGdefWbs